Tantangan Kebijakan Affirmative Action Sebagai Upaya Penguatan Keterwakilan Perempuan di Legislatif [Challenges of Affirmative Action as An Effort to Strengthen Women's Representation in The Legislature] - Tias, Rahma Ning; Nisrina, Awalia Dhia; Destriputra, Nabil; Al Putra, Ferdian Ahya; Prakoso, Septyanto Galan (Sekretariat Jenderal DPR RI, 2023)
The idea of at least 30% representation of women in nominations for DPR and DPRD members is a form of state's effort to provide affirmative action for women in the political sphere. The state's efforts to provide affirmative action for women in the political sphere aim to strengthen women's representation in the legislature. This affirmative action increased women's representation in the legislative from period to period. Even in the 2019-2024 period, the percentage of women in the DPR was 20% or 118 seats out of the total number of members, which is the first time that women's representation in the DPR has reached this figure. However, the increase in women's representation in the DPR is not in line with their contribution in the field of legislation. Descriptive qualitative research methods with library study data collection techniques were used to provide a comprehensive picture of the situation in accordance with the facts at the time the research was conducted, with an emphasis on the challenges of affirmative action policies. This article aims to analyze the challenges of the government's affirmative action policy in the form of a minimum quota for women in nominations for DPR members of at least 30% as an effort to strengthen women's representation in the legislature. The results found relate to the challenges of affirmative action that have not maximized the role of women in legislative institutions: women's capacity that has not been maximized, patriarchal culture, and women's representation as a formality.AbstrakGagasan mengenai keterwakilan perempuan paling sedikit 30% dalam pencalonan anggota DPR dan DPRD merupakan bentuk usaha negara dalam memberikan affirmative action untuk perempuan di lingkup politik. Upaya negara dalam memberikan affirmative action untuk perempuan di lingkup politik bertujuan untuk menguatkan keterwakilan perempuan di legislatif. Kebijakan afirmatif ini kemudian membuahkan hasil berupa meningkatnya keterwakilan perempuan di lembaga legislatif dari periode ke periode. Bahkan di periode 2019-2024 persentase perempuan di DPR sebesar 20% atau sebanyak 118 kursi dari total jumlah anggota, yang mana ini pertama kalinya keterwakilan perempuan di DPR menyentuh angka tersebut. Namun, peningkatan keterwakilan perempuan di DPR tidak sejalan dengan kontribusi mereka di bidang legislasi. Metode penelitian kualitatif deskriptif dengan teknik pengumpulan data studi pustaka digunakan untuk memberikan gambaran komprehensif tentang situasi yang sesuai dengan fakta pada saat penelitian dilakukan, dengan penekanan pada tantangan kebijakan affirmative action. Tulisan ini bertujuan untuk menganalisis tantangan kebijakan affirmative action pemerintah berupa kuota minimal perempuan dalam pencalonan anggota DPR minimal 30% sebagai upaya penguatan keterwakilan perempuan di legislatif. Hasil yang ditemukan sehubungan dengan tantangan kebijakan affirmative action yang belum memaksimalkan peran perempuan di lembaga legislatif yakni kapasitas perempuan yang belum maksimal, budaya patriarki, serta keterwakilan perempuan sebagai formalitas.